Habilitation à diriger des recherches d'Abdeljalil SGHARI - Abdeljalil Sghari (Physio-Géo)
The document provides an overview of investigations which were sanctioned by an accreditation to supervise research. It presents two parts: the first is devoted to the geomorphological evolution of southern Tunisia during the Tertiary-Quaternary transition and the second to the actual valorization of the natural environment of this region.